Effects of nano eggshell powder as a sustainable bio-filler on the physical, rheological, and microstructure properties of bitumen - Zghair Chfat, Alattafi Hadi; Haryati, Yaacob; Nurul Hidayah, Mohd Kamaruddin; Al-Saffar, Zaid Hazim; Putra Jaya, Ramadhansyah (Elsevier B.V., 2024)
Improving bitumen properties to withstand traffic loads and environmental conditions is essential for prolonging pavement life. Given that nanomaterials stand as potential candidates to fulfil these requirements, this study focused on the potential use of nano eggshell powder (NESP) as a sustainable additive in bitumen. NESP was produced using a top-down approach with a ball milling machine. Then, 0% (control), 1%, 3%, 5%, 7%, and 9% NESP by weight of bitumen PEN 60/70 was added. Storage stability and X-Ray Diffraction (XRD) tests were performed to assess the compatibility and dispersion of NESP within the bitumen matrix. Penetration, softening point, ductility, viscosity, and dynamic shear rheometer (DSR) tests were performed to assess the physical and rheological properties of the modified bitumen. Fourier Transform Infrared (FTIR), Atomic Force Microscopy (AFM), contact angle, and thermal analysis (TGA) tests were conducted to analyze the microstructure properties. The results from storage stability tests and XRD patterns suggested that NESP was effectively integrated and evenly dispersed within the bitumen matrix. The incorporation of NESP led to improvement in the hardness and cohesion of the bitumen, as evidenced by reductions in penetration and increase in the softening point. However, higher concentrations of NESP resulted in decreased ductility of the bitumen. The addition of NESP into the bitumen resulted in increased viscosity and improved resistance to aging and rutting. Furthermore, the adhesion and thermal properties of bitumen improved with higher NESP content. Notably, the most effective concentration for enhancing bitumen properties was found to be 9% NESP.